Opinion formation model in a hierarchical society - Romero Longar, Maria Celeste (2021)
In this work we study the formation of consensus in a hierarchical populations. We derive the corresponding kinetic equations, analyze the long time behavior of their solutions, and characterize the consensus opinion.